A Review of Technical Advances, Barriers, and Solutions in the Power to Hydrogen (P2H) Roadmap. (December 2020) - Hu, Guoping; Chen, Chao; Lu, Hiep Thuan; Wu, Yue; Liu, Congmin; Tao, Lefu; Men, Yuhan; He, Guangli; Li, Kevin Gang
Graphical abstract: Abstract: Power to hydrogen (P2H) provides a promising solution to the geographic mismatch between sources of renewable energy and the market, due to its technological maturity, flexibility, and the availability of technical and economic data from a range of active demonstration projects. In this review, we aim to provide an overview of the status of P2H, analyze its technical barriers and solutions, and propose potential opportunities for future research and industrial demonstrations. We specifically focus on the transport of hydrogen via natural gas pipeline networks and end-user purification. Strong evidence shows that an addition of about 10% hydrogen into natural gas pipelines has negligible effects on the pipelines and utilization appliances, and may therefore extend the asset value of the pipelines after natural gas is depleted. To obtain pure hydrogen from hydrogen-enriched natural gas (HENG) mixtures, end-user separation is inevitable, and can be achieved through membranes, adsorption, and other promising separation technologies. However, novel materials with high selectivity and capacity will be the key to the development of industrial processes, and an integrated membrane-adsorption process may be considered in order to produce high-purity hydrogen from HENG. It is also worth investigating the feasibility of electrochemical separation (hydrogen pumping) at a large scale and its energy analysis. Cryogenics may only be feasible when liquefied natural gas (LNG) is one of the major products. A range of other technological and operational barriers and opportunities, such as water availability, byproduct (oxygen) utilization, and environmental impacts, are also discussed. This review will advance readers' understanding of P2H and foster the development of the hydrogen economy.